ANALISIS DEIKSIS DALAM NOVEL BERJALAN DALAM KABUT KARYA KAREN KINGSBURY - Ndruru, Megasari (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Deixis is one of the objects of pragmatic studies which examines demonstrative words in conversation and of course in a literary work, especially novels, there are also several deixis, including person, demonstrative, place, time and discourse deixis. This research aims to describe deixis in the novel Walking in the Mist by Karen Kingsbury. The type of research is qualitative research with a content/document analysis approach. The data collected by researchers came from the novel "Walking in the Mist" by Karen Kingsbury, in the form of text data taken after reading the novel repeatedly. The results of this research found the use of "pointer" deixis in several paragraph quotations, such as examples of persona deixis which refer to people or replace someone (I, you, you, you, us, us, they, he, she, my, and his). Use of demonstrative deixis (this and that). Use of place deixis (here, there, and there). Use of time deixis (now, tomorrow, next week, today, this week, yesterday, yesterday afternoon, next year, last fall, and tonight. And then the use of discourse deixis. The suggestion from researchers is that this research should be (1 ) Become a reference and as a reference for further research. (2) For readers, it should increase insight and knowledge about pragmatics, especially deixis (denotation). (3) Research on pragmatics needs to be carried out both in the pragmatics of a language and pragmatics in literary works in general, in particular deixis. This is because deixis never escapes in our life when communicating.